Homozygous Familial Hypercholesterolaemia with Valvular Aortic Stenosis and Significant Coronary Artery Disease: A Case Report (Cardiovascular Journal, 2014)
Homozygous Familial Hypercholesterolaemia is a genetic disorder which usually presents with early cardiovascular disease ranging from premature ischaemic disease, including myocardial infarction to aortic root stenosis. A 21 year old Bangladeshi male presented with exertional chest pain and breathlessness. He was diagnosed as a case of Homozygous Familial Hypercholesterolaemia. His angina symptoms were due to underlying valvular aortic stenosis which is a rare presentation of Homozygous Familial Hypercholesterolaemia. DOI: http://dx.doi.org/10.3329/cardio.v6i2.18365 Cardiovasc. j. 2014; 6(2): 180-183